Method of time resolved refractive index measurements of x-ray laser heated solids - Williams, G; Chung, H; Vinko, S; Kuenzel, S; Sardinha, AB; Zeitoun, P; Fajardo, M (2013)
With the advent of new x-ray light-sources worldwide, the creation of dense, uniformly heated plasma states arising from intense x-ray irradiation of solids has been made possible. In the early stages of x-ray solid heating, before significant hydrodynamic motion occurs, the matter exists in a highly non-equilibrium state. A method based on wavefront sensing is proposed to probe some of the fundamental properties of these states. The deflection and absorption of a high harmonic probe beam propagated through the plasma can be measured with a wavefront sensor, and allow for the determination of the complex refractive index (RI) of the plasma, giving a 2D map of the optical properties as function of time in a pump-probe arrangement. A solid heating model has been used to estimate the expected temperatures of x-ray heated thin foils, and these temperatures are used in three separate models to estimate the changes in the refractive index. The calculations show the changes induced on an extreme ultra-violet (XUV) probe beam by a solid density thin foil plasma are significant, in terms of deflection angle and absorption, to be measured by already existing XUV Hartmann wavefront sensors. The method is applicable to a wide range of photon energies in the XUV (10 s to several 100 s of eV) and plasma parameters, and can add much needed experimental data to the fundamental properties of such dense plasma states. © 2013 American Institute of Physics.